Contribution to the Mexican Hyperaspidini: Hyperaspis picta (Gorham, 1899) comb. nov. (Coleoptera: Coccinellidae) - Szawaryn, Karol; Nestorarriola, Jorge Ismael (Zootaxa, 2025)
This study presents a detailed morphological analysis of the previously neglected genus Semra Özdikmen (=Cinachyra Gorham), following the discovery of a female specimen and the re-examination of the male holotype. The analysis reveals that Semra shares key characteristics with the genus Hyperaspis Chevrolat from the tribe Hyperaspidini, supporting the synonymization of both genera, as a result a new combination Hyperaspis picta comb. nov. is proposed. Despite this, Hyperaspis picta remains very distinctive species due to its unique coloration and surface texture, setting it apart from other American species of Hyperaspis.